Solution Processed Tungsten Oxide Interfacial Layer for Efficient Hole‐Injection in Quantum Dot Light‐Emitting Diodes. Issue 2 (5th August 2013) - Yang, Xuyong; Mutlugun, Evren; Zhao, Yongbiao; Gao, Yuan; Leck, Kheng Swee; Ma, Yanyan; Ke, Lin; Tan, Swee Tiam; Demir, Hilmi Volkan; Sun, Xiao Wei
<x xml:space="preserve">Abstract</x> A highly efficient and stable QLED using an inorganic WO3 nanoparticle film as a hole injection layer is demonstrated.The resulting WO3 nanoparticle‐based QLEDs also exhibit superior performance compared to that of the present PEDOT:PSS‐based QLEDs. The results indicate that WO3 nanoparticles are promising solution‐processed buffer layer materials and serve as a strong candidate for QLED technology towards the practical applications in the next‐generation lighting and displays. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>